2016
DOI: 10.1097/md.0000000000002302
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 3 is Associated With the Risk of HCV Infection and HBV-Related Diseases

Abstract: There are inconsistent data on the association of risk of hepatitis virus infection and hepatitis virus-related diseases with the toll-like receptor 3 (TLR3) gene.Several common polymorphism sites were targeted to assess the risk of HBV infection, HCV infection, and HBV-related diseases.Meta-analysis combining data for 3547 cases and 2797 controls from 8 studies was performed in this study. Pooled ORs were calculated to measure the risk of hepatitis virus infection and hepatitis virus-related diseases. Fixed-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…Huang et al (Huang et al, 2015) indicated that the TT genotype of TLR3 rs3775290 is closely correlated with a decreased risk of CHB. A meta-analysis by Geng et al (Geng et al, 2016) demonstrated a significant effect of TLR3 rs3775291 and HBV-related diseases.…”
Section: Chronic Hbv Infectionmentioning
confidence: 99%
“…Huang et al (Huang et al, 2015) indicated that the TT genotype of TLR3 rs3775290 is closely correlated with a decreased risk of CHB. A meta-analysis by Geng et al (Geng et al, 2016) demonstrated a significant effect of TLR3 rs3775291 and HBV-related diseases.…”
Section: Chronic Hbv Infectionmentioning
confidence: 99%
“…Indeed, Sá et al, 2015, demonstrated that the rs5743305 and rs3775291 SNPs were not associated with a risk for HCV infection [32]. This was inconsistent with a study by Medhi et al, 2011, that analyzed polymorphisms at the promoter region of the TLR3 gene [33], as well as a recent meta-analysis that concluded TLR3 gene polymorphisms (mainly rs3775291) were associated with a risk for HCV infection [34]. This inconsistency may be explained by the involvement of genetic factors due to racial and ethnic differences, as well as controversies in regard to whether TLR3 expression is upregulated [35, 36] or downregulated [37, 38] in peripheral blood mononuclear cells from patients with chronic HCV.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) within the TLR3 gene may cause changes in the protein or gene expression, which affects the function and efficacy of signal transduction and thus an altered immune response. In previous reports, TLR3 polymorphisms rs1879026, rs3775296, rs3775291, rs5743305 have been associated with the outcome of hepatitis C virus (HCV) and HBV infection, and the development of consequential liver cirrhosis and HCC primarily in Asian populations 14 . Similarly, Al-Qahtani et al .…”
Section: Introductionmentioning
confidence: 99%
“…This study investigates the presence of the TLR3 SNPs rs3775291 and rs5743305 in a large multicentre cohort of patients with HBV infection and healthy controls of Caucasian ethnicity. We selected these SNPs as they have recently been found to represent new risk factors of HBV-related diseases in an Asian population 14 and affect TLR3 signalling 17 19 . We aimed to assess the impact of these SNPs on the susceptibility of chronic HBV infection (CHB), spontaneous HBsAg seroclearance (SC) and the occurrence of different disease stages of CHB such as HBeAg SC and inactive carrier (IC) state.…”
Section: Introductionmentioning
confidence: 99%